OP35 The relationship between exposure to gambling-related advertising and attitudes, behaviour and gambling-related harms. (26th August 2022) - Goyder, Elizabeth; McGrane, Ellen; Wardle, Heather; Clowes, Mark; Blank, Lindsay; Pryce, Robert; Field, Matthew
Abstract : Background: There is increasing public support for restrictions on gambling advertising related to greater awareness of the risk of gambling-related harms to both individuals and the wider community. Further development of the evidence base is required to support the development of evidence-informed policy in this field. We aimed to evaluate the scope and limitations of current evidence on the association between exposure to gambling related advertising and attitudes, behaviour and gambling related harms. Methods: We undertook a systematic review of previous reviews and reports that included evidence on the impact of gambling advertising and which had used systematic methods for evidence identification and synthesis. We conducted searches of relevant databases, including Web of Science and PsycInfo, for reviews published January 2000 to January 2022 and searched the websites of relevant government bodies, charities and industry organisations. We consulted topic experts to identify reviews that were unpublished or not identified by our searches, and undertook reference and citation searches. Review level evidence was extracted, synthesised and quality assessed. We reviewed the types and nature of available evidence, reporting the strengths and limitations of research to date and identifying where there were significant evidence gaps. Results: Initial database searches identified 1024 unique papers of which four met inclusion criteria; websites searches identified a further three commissioned reviews and two unpublished reviews were identified by topic experts, giving a total of nine systematic reviews that met inclusion criteria. Of these, two covered all forms of advertising and all populations; seven were limited by advertising type or population focus. Overall there was most evidence for a relationship between exposure to advertising and attitudes, behaviour and potential harmful gambling for those already experiencing problems related to gambling, with more limited evidence on children and young people. Most evidence was based on self-reported exposures and behaviours, both of which may be subject to response bias. There was a dearth of evidence on the relationship between exposure to advertising and risk of harm for other vulnerable groups. Few studies evaluated the impact of implementing advertising restrictions on gambling or related harms. Conclusion: There is a growing evidence base that supports an association between advertising and potentially harmful gambling activity, particularly for those already experiencing gambling harms. Evaluation of the impact of changes to advertising regulations are needed to explore whether it is possible to demonstrate a population level relationship between exposure, attitudes, behaviour and harms.